PERBEDAAN KEPUTUSAN MAHASISWA DALAM MEMILIH STIE DI JAWA TIMUR - Nur Handayani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
This research aim is to know the factors which influence student in selecting STIE in east java and to know factor differences which influence student’s decision in selecting STIESIA Surabaya,STIE Perbanas and STIE Malangkucecwara.This research population is college student in the second semester of 2003/2004. Data analysis technique uses .factor analysis and discriminant analysis. Factor analysis result indicates that proposed hypothesis is can not be rejected or there are several factors which influence the student’s decision differences in  selecting STIE (13 variables in 12 .factors).  Discriminant analysis result indicates that the variables which are differenciate the decision. The variables are divided in two factors, which are internal factor and eksternal  factor. Internal  factor consists of (1) reguler learning system, (2) school  fee credit, while eksternal factor consists of (I) health facility, clean environment and (3) boarding house location.